Upaya Peningkatan Kesehatan melalui Program Penjaringan Kesehatan Gigi dan Mulut Kelas 3 SDN Gejayan Tahun 2017 - Elvira Purnamasari; Sukma Wilis Wijaya; Rizki Gisma Wandari; Aini Fajri Karimah; Dini Hapsari (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
Dental and oral health is an integral part of overall health. This can affect speech, swallowing and self-confidence. Children are very susceptible to dental caries due to sweet food habits and lack of dental and oral hygiene practices. This is supported by the age of children who experience missing teeth, teeth growing and the phase of mixed teeth.Dental and oral health screening activities aim to analyze and detect early childhood dental and oral health so that appropriate health programs can then be determined. This activity was carried out in April 2017 with the target of grade 3 children at SDN Gejayan. The method used is anamnesis, clinical examination and filling out questionnaires. From the results of the study, the dental and oral hygiene of grade 3 children at SDN Gejayan was moderate, with a prevalence of 100% dental caries and 0% PTI. Healthy gum health status. 42.8% of students brush their teeth 2-3 times a day in the morning and evening. Most visit the dentist only when sick. The education level of the father and mother is equivalent to undergraduate and senior high school. The occupations of father and mother are self-employed and housewives. The conclusions of the dental and oral health screening activities include: (1) moderate dental and oral hygiene status, (2) caries prevalence is 100% with PTI of 0%, (3) all students have healthy gum health status, (4) students brush their teeth 2 times a day and 3 times a day in the morning and evening, (5) students visit the dentist only when sick.